KINERJA PEMIMPIN PEREMPUAN DI SEKTOR PENDIDIKAN DI ACEH - Pratiwi Dwi Suhartanti; Abdul Rahman Lubis; Nurdasila Darsono (Departemen Manajemen, Universitas Syiah Kuala, 2017)
ABSTRACT Female leadership in Aceh has become a very fascinating topic. From gender point of view, there is a stigma that men are considered more superior than women. This is reflected by the female leaders’ percentage being far ahead from male leaders’. In the education sector in Aceh, there has been difference on the number of headmasters and headmistresses in A-accredited Senior High Schools. In almost all levels of education, there are many more headmasters than headmistresses. Yet, there is a phenomenon on leadership in education sector in Aceh, in which gender equality in principal election has emerged. Individual competence, work motivation and good communication style are expected to improve headmistresses’ leadership quality in Aceh so their performance is also enhanced. This study aims to notice influences of individual competence, motivation and communication style towards leadership and their impacts to the headmistresses’ performance in Aceh. By applying Slovin formula, there were 220 teachers participating as study samples. They were distributed proportionally to 10 A-accredited Senior High Schools in Aceh led by headmistresses. Questionnaires were used to collect data. The data was then analyzed using SEM with the help of AMOS 22.0 program. The study result showed that individual competence, work motivation and communication style significantly affected leadership and headmistresses’ performance. The other result showed that individual competence, work motivation and communication style affected headmistresses’ performance through leadership. Keywords: Communication Style, Work Motivation, Individual Competence, Leadership, Performance